Approaches for targeting the mycobactin biosynthesis pathway for novel anti-tubercular drug discovery: where we stand. (3rd July 2022) - Shyam, Mousumi; Shilkar, Deepak; Rakshit, Gourav; Jayaprakash, Venkatesan
ABSTRACT: Introduction: Several decades of antitubercular drug discovery efforts have focused on novel antitubercular chemotherapies. However, recent efforts have greatly shifted toward countering extremely/multi/total drug-resistant species. Targeting the conditionally essential elements inside Mycobacterium is a relatively new approach against tuberculosis and has received lackluster attention. The siderophore, Mycobactin, is a conditionally essential molecule expressed by mycobacteria in iron-stress conditions. It helps capture the micronutrient iron, essential for the smooth functioning of cellular processes. Areas covered: The authors discuss opportunities to target the conditionally essential pathways to help develop newer drugs and prolong the shelf life of existing therapeutics, emphasizing the bottlenecks in fast-tracking antitubercular drug discovery. Expert opinion: While the lack of iron supply can cripple bacterial growth and multiplication, excess iron can cause oxidative overload. Constant up-regulation can strain the bacterial synthetic machinery, further slowing its growth. Mycobactin synthesis is tightly controlled by a genetically conserved mega enzyme family via up-regulation (HupB) or down-regulation (IdeR) based on iron availability in its microenvironment. Furthermore, the recycling of siderophores by the MmpL-MmpS4/5 orchestra provides endogenous drug targets to beat the bugs with iron-toxicity contrivance. These processes can be exploited as chinks in the armor of Mycobacterium and be used for new drug development.